2016
DOI: 10.1037/dev0000157
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced attention to speaking faces versus other event types emerges gradually across infancy.

Abstract: The development of attention to dynamic faces vs. objects providing synchronous audiovisual vs. silent visual stimulation was assessed in a large sample of infants. Maintaining attention to the faces and voices of people speaking is critical for perceptual, cognitive, social, and language development. However, no studies have systematically assessed when, if, or how attention to speaking faces emerges and changes across infancy. Two measures of attention maintenance, habituation time (HT) and look-away rate (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 80 publications
(161 reference statements)
2
24
0
1
Order By: Relevance
“…Attention to orofacial gestures enhances speech processing in infants (Burnham & Dodd, 2004;Teinonen, Aslin, Alku, & Csibra, 2008) and in adults (Lansing & McConkie, 1999). This enhanced attention to dynamic gaze, facial and vocal cues emerges early in the first year of life (Bahrick, Todd, Castellanos, & Sorondo, 2016;Farroni, Mansfield, Lai, & Johnson, 2003;Senju & Csibra, 2008). The development of these multisensory processes is highly experience-dependent, as exemplified by perceptual narrowing and tuning to facial and speech patterns most prevalent in the child's native environment (Pascalis et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Attention to orofacial gestures enhances speech processing in infants (Burnham & Dodd, 2004;Teinonen, Aslin, Alku, & Csibra, 2008) and in adults (Lansing & McConkie, 1999). This enhanced attention to dynamic gaze, facial and vocal cues emerges early in the first year of life (Bahrick, Todd, Castellanos, & Sorondo, 2016;Farroni, Mansfield, Lai, & Johnson, 2003;Senju & Csibra, 2008). The development of these multisensory processes is highly experience-dependent, as exemplified by perceptual narrowing and tuning to facial and speech patterns most prevalent in the child's native environment (Pascalis et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the protocol is simple enough for infants and children to show reliable intersensory matching. Further, despite using a common protocol, participants of different ages will likely show selective attention to different properties of the events and use different processing strategies (see Bahrick, 2001; Bahrick, Todd, Castellanos, & Sorondo, 2016; Franchak, Heeger, Hasson, & Adolph, 2016; Frank, Vul, & Saxe, 2012). For older children and adults, the linguistic content of the social events may be more salient as their attention and language skills mature and affect speech perception and audiovisual processing (for related ideas see Bowerman & Levinson, 2001; Frank, Vul, & Saxe, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These 127 infants were part of a larger study in which mean performance for a variety of variables was reported, including total time to habituation, the look-away rate during habituation, the mean duration of the first two habituation trials, mean looking time over test trials, and visual recovery scores [2,31]. The durations of infants’ individual looks and the durations of total looking times within individual trials—the focus of the current study—have not been published.…”
Section: Methodsmentioning
confidence: 99%